2019
DOI: 10.3390/f10020186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arbuscular Mycorrhizal Fungi on Growth, Photosynthesis, and Nutrient Uptake of Zelkova serrata (Thunb.) Makino Seedlings under Salt Stress

Abstract: Salinity is the primary restriction factor for vegetation conservation and the rehabilitation of coastal areas in Eastern China. Arbuscular mycorrhizal fungi (AMF) have been proved to have the ability to alleviate salt stress in plants. However, the role of AMF in relieving salt stress among indigenous trees species is less well known, limiting the application of AMF in the afforestation of local area. In this study, a salt-stress pot experiment was conducted to evaluate the effects of AMF on Zelkova serrata (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 54 publications
6
28
0
Order By: Relevance
“…The F. mosseae 1 and F. mosseae 2 strains, isolated from different soil conditions by staff at the Beijing Academy of Agriculture and Forestry Science, showed no significantly different effects on the growth and nutrient concentrations of G. sinensis seedlings. Similar results were also found on Z. serrata seedlings [19]. The correlation analysis between mycorrhizal dependency and increased nutrient accumulation indicated that increased biomass by AMF was significantly associated with increased P and K content in all three organs, and with N content in the leaf and stem.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The F. mosseae 1 and F. mosseae 2 strains, isolated from different soil conditions by staff at the Beijing Academy of Agriculture and Forestry Science, showed no significantly different effects on the growth and nutrient concentrations of G. sinensis seedlings. Similar results were also found on Z. serrata seedlings [19]. The correlation analysis between mycorrhizal dependency and increased nutrient accumulation indicated that increased biomass by AMF was significantly associated with increased P and K content in all three organs, and with N content in the leaf and stem.…”
Section: Discussionsupporting
confidence: 81%
“…Photosynthetic pigments and photosynthetic parameters being enhanced by AMF has been reported by a number of researchers [12,19]. Our results showed that Chl and Chl a concentrations were increased after inoculation with each of the AMF strains.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The leaf relative water content (RWC) was measured according to the previous method described by Wang et al (2019) using the following formula: RWC = (FW -DW) / (TW -DW) x 100%, where FW is fresh weight, DW is dry weight, and TW is turgid weight obtained after the leaf was soaked for 24 h in deionized water. The membrane stability index (MSI) was estimated according to the method described by Talaat and Shawky (2014) using the formula: MSI = (1 -C1/C2) x 100%, where C1 is the electrical conductivity bridge after the leaves were heated at 40 °C for 30 min in a water bath and C2 is the electrical conductivity bridge after the leaves were boiled at 100 °C in a boiling water bath for 10 min.…”
Section: Measurement Of Relative Water Content and Membrane Stabilitymentioning
confidence: 99%